Summarizing Topics: From Word Lists to Phrases - Hannah, Lauren A.; Wallach, Hanna (NIPS Workshop on Modern Machine Learning and Natural Language Processing, 2014)
In this paper, we present a two-stage approach to generating descriptive phrases from the output of a statistical topic model, such as LDA [4].